Does green finance promote enterprises’ green technology innovation in China? - Jiang, Shuangshuang; Liu, Xiaojiao; Liu, Zhonglu; Shi, Hao; Xu, Hongdi (Frontiers in Environmental Science, 2022)
In the carbon neutrality strategy, understanding the effects of green finance on green technology innovation is conductive to promoting the green transformation of the economy. Based on the micro-level and provincial panel data of Shanghai and Shenzhen A-share listed companies from 2012 to 2019, this study explored the impact of green financial development on the enterprises’ green technology innovation. Both mediating effect and moderating effect models were employed to determine the impact of green finance on green technological innovation. It was found that green finance significantly improved the enterprises’ green technology innovation, despite sufficient incentives for “quantity” and relatively insufficient motivation for “quality”. The mechanistic tests demonstrated that the green finance could encourage enterprises to improve green technology innovation by alleviating corporate financing constraints. The green innovation effect of green finance was gradually increased when the regional intellectual property protection was improved. The heterogeneity test indicated that the incentive effect of green financial development on green technology innovation was more evident in state-owned enterprises, enterprises with good internal control quality, and enterprises in the growth period. If only enterprises in the recession stage received green financial support, a “green innovation bubble” might occur. The research conclusions enrich the theories on the driving factors of enterprise green innovation and provide empirical evidence for enhancing the competitiveness of enterprise green innovation and achieving carbon neutrality.